Investigating the Use of Artificial Intelligence in Journalism and its Impact on News Quality in Pakistan - Rizwan, Muhammad; Dr. Wajid Zulqarnain; Dr.Haroon Elahi (Journal of Peace, Development and Communication, 2024)
Technology transfer entails the dissemination of innovative technology from one nation or organization to another. This process typically involves the exchange of knowledge and expertise rather than physical hardware, with the primary focus on effectively communicating the underlying mechanisms and designs. Successful technology transfer is contingent upon clear communication, which also facilitates persuading the original technology owner to share their innovations with other countries. Factors such as economic considerations and location feasibility also play a role in technology transfer. Pakistan has yet to fully integrate artificial intelligence (AI) into its media industry. Enhancing communication with countries that possess advanced AI technology, such as China and the United States, could potentially facilitate the introduction of AI-driven journalism in Pakistan. To improve international communication for technology transfer, this study will conduct in-depth interviews with experts in the field, analyzing their insights to develop optimal communication strategies. This research find out the several factors can be effectivetly contribute the usage of AI in journalism in Pakiatan and enhance the news quality. These recommendations can then be presented to the relevant government agencies for implementation.